Education in Medical Informatics in The Netherlands: A Nationwide Policy and The Erasmus Curriculum - van Bemmel, J. H.; SoUet, P. C. G. M.; Grashuis, J. L. (Methods of Information in Medicine, 1989)
The curricula of all Medical Faculties still bear the characteristics of an era in which the physician was not educated in managing medical information systems, using communication networks, and processing knowledge. In attempting to formulate the prerequisites for developing and adjusting future curricula, we discuss the evolution of medical information technology during the past 25 years and give examples to illustrate that, by extrapolating current trends, future developments in information technology, medicine and education can be predicted. A plea is made for a strong interaction between scientific developments in medical informatics and academic education. In addition, a model based on our experience in medical informatics education of over 15 years, is pointed out. Furthermore, a nationwide policy on medical informatics in The Netherlands, is discussed. Our treatise is concluded by presenting the outline of the curriculum in medical informatics at the Erasmus University in Rotterdam. Educational recommendations conclude the paper.
Keywords: Medical Informatics; Curricula; Information Technology; Knowledge Processing